Participaç\~ao no mercado de trabalho e violência doméstica contra as mulheres no Brasil - Daniel Cerqueira; Rodrigo Leandro de Moura; Wânia Pasinato Izumino (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– A subject of great relevance, but little studied in Brazil, concerns the effect of female participation in the labor market (PFMT) on domestic violence. In this article, we try to understand this question from a reflection on two polar literatures based on economic rationality and patriarchal theory, which reach opposite conclusions. Additionally, based on PNAD/IBGE data from 2009, we examined empirically the effects of PFMT on the violence perpetrated not only by the spouse but also by the former spouse. In order to overcome the potential problems of endogeneity, we used a probit model with instrumental variables, in which the instrument for the participation of women in the labor market was based on the number of places in kindergartens and pre-schools in the locality where they live.
Keywords: J15; J16; K42; 330; domestic violence; Brazil; job Market; rationality; patriarchy